Business policy and strategy in Nigeria : case studies of successful business organisations - Essien-Obot, Amayak E. ([Jos, Nigeria] : Jos University Press, 1999)
Aims at promoting the process of capacity building in the area of business studies in Nigeria. It deliberately seeks to marry theoretical framework to business practice, compare monopoly with competition, promote the concept of strategic management and pay attention to businesses of different sizes.
Includes bibliographical references and index.
oif 23/03/15; 12/08/15
Loan
Keywords: Strategic planning -- Nigeria; Strategic planning -- Nigeria -- Case studies; Business planning -- Nigeria -- Case studies; Business planning -- Nigeria